1994
DOI: 10.1002/yea.320100413
|View full text |Cite
|
Sign up to set email alerts
|

I. Yeast sequencing reports. Sequencing of chromosome I of Saccharomyces cerevisiae: Analysis of the 42 kbp SP07CENICDC15 region

Abstract: Determination of the DNA sequence and preliminary functional analysis of a 42 kbp centromeric section of chromosome I have been completed. The section spans the SPO7-CEN1-CDC15 loci and contains 19 open reading frames (ORFs). They include an apparently inactive Ty1 retrotransposon and eight new ORFs with no known homologs or function. The remaining ten genes have been previously characterized since this part of the yeast genome has been studied in an unusually intensive manner. Our directed sequencing allows a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…We cannot conclude whether this ORF codes for a yeast PDI, but a related function is not to be excluded. A data base search showed that the tRNA alanine (UGC) sequence deduced from this gene corresponds to the DNA sequence published by Drabkin and RajBhandary (1985) for this tRNA species and later assigned to chromosome I (Clark et al, 1994). Therefore this is the second gene described for this tRNA species.…”
Section: Orfs Showing a Similarity With Known Genessupporting
confidence: 59%
“…We cannot conclude whether this ORF codes for a yeast PDI, but a related function is not to be excluded. A data base search showed that the tRNA alanine (UGC) sequence deduced from this gene corresponds to the DNA sequence published by Drabkin and RajBhandary (1985) for this tRNA species and later assigned to chromosome I (Clark et al, 1994). Therefore this is the second gene described for this tRNA species.…”
Section: Orfs Showing a Similarity With Known Genessupporting
confidence: 59%
“…This appears to be the case for chromosomes I11 and XIV, where five pairs of duplicate genes (coding for three proteins and two tRNAs) have been found flanking the centromeres, but these are interspersed with genes unique to one chromosome (Lalo et al, 1993). Extensive sequence data around centromeres is at present only available for six of the 16 yeast chromosomes: I, 11, 111, IV, XI and XIV (Clark et al, 1993;this study;Oliver et al, 1992;Mann and Davis, 1986;Dusterhoft and Philippsen, 1992;Lalo et al, 1993), and already two pairs of duplicate centromeres are apparent. Since duplication of a centromere is likely to lead to (Chen et al, 1993; nucleotides 1518-2222 of database accession number L07603) and Streptomycesfradiae (Siemieniak et al, 1990; nucleotides 47445109 and 51 11-5521 of accession number M29297).…”
Section: Similarity Between the Cen2 And Cen4 Regionsmentioning
confidence: 95%
“…Erp2 is a member of the p24 family involved in ER to Golgi transport [28]. FUN14 encodes a protein of so far unknown function (Function unknown now, [29]) that was found in two high-throughput studies to be a mitochondrial protein [30,31]. We cloned the FUN14 coding sequence in an ARS/CEN plasmid containing a rather strong triose phosphate isomerase (TPI) promoter.…”
Section: Mcp3 Is a High-copy Suppressor Of Cells Lacking Mdm10mentioning
confidence: 99%